PVDF-based solid electrolyte and preparation method thereof
By introducing DMMSA into the hybrid system of PVDF and LiTFSI, a deep eutectic solvent system is formed and the PVDF solid electrolyte is modified, which solves the problems of low ionic conductivity and high interface resistance, and achieves higher conductivity and lower interface impedance, while maintaining thermal stability, and has wide application potential.
Patent Information
- Application Number
- CN202510069010.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
AI Technical Summary
The existing PVDF-based solid electrolytes have problems with low ionic conductivity and high interface resistance, which limits their application in lithium-ion batteries.
By introducing N,N-dimethylmethanesulfonamide (DMMSA) into a mixed system of PVDF and LiTFSI, a deep eutectic solvent (DES) system is formed to modify the PVDF solid electrolyte.
It improves the ionic conductivity of PVDF-based solid electrolyte, reduces the interface resistance, maintains good thermal stability, simplifies the processing process, and has the potential to be applied to solid-state batteries on a large scale.
Smart Images

Figure HDA0005245122450000011 
Figure HDA0005245122450000012 
Figure HDA0005245122450000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a PVDF-based solid electrolyte and a preparation method thereof, and a quasi-solid-state battery. Background Art
[0002] Since the commercial application of lithium-ion batteries, 3C products have been constantly updated, power battery vehicles have developed rapidly, and the requirements for lithium-ion batteries have become increasingly higher. Traditional liquid lithium-ion batteries inevitably volatilize and decompose due to the electrolyte, causing serious safety problems. Solid electrolytes have excellent safety performance due to the theoretical non-existence of liquid electrolytes, and take into account stable cycle life and good energy density. They have been widely studied in recent years.
[0003] Polyvinylidene fluoride (PVDF) has excellent electrochemical properties, high mechanical strength, good processing performance and high compatibility. It can be combined with different lithium salts to prepare solid electrolyte films, showing great application prospects in the field of quasi-solid-state batteries and all-solid-state batteries.
[0004] At present, the development of PVDF single polymer solid electrolyte is restricted by the problems of low ionic conductivity and high interface resistance. In this regard, some modification strategies such as introducing inorganic fillers, forming copolymers, adding plasticizers, etc. have been studied in depth to improve the ionic conductivity of the electrolyte and optimize the interface contact. However, the effects of these methods are often limited and may introduce new problems such as the decline of mechanical properties of the electrolyte, poor thermal stability, and complex processing, which are not enough to significantly improve the performance of the battery.
[0005] In summary, there is still a need to study technical solutions that can improve the ionic conductivity of PVDF-based solid electrolytes while reducing the interface resistance and maintaining good thermal stability with simple processing methods. Summary of the invention
[0006] The object of the present invention is to provide a technical solution which can improve the ionic conductivity of a PVDF-based solid electrolyte while reducing the interface resistance and maintaining good thermal stability and has a simple processing method.
[0007] In order to achieve the above object, the present invention provides the following technical solutions.
[0008] In a first aspect, the present invention provides a method for preparing a PVDF-based solid electrolyte, wherein the method comprises:
[0009] Polyvinylidene fluoride (PVDF), lithium salt lithium bistrifluoromethanesulfonyl imide (LiTFSI), N,N-dimethylmethanesulfonamide (DMMSA), and an organic solvent are mixed and stirred to obtain a gel solution;
[0010] The gel solution is dried to obtain a PVDF-based solid electrolyte.
[0011] The preparation method of the PVDF-based solid electrolyte material provided by the present invention introduces DMMSA into the mixed system of PVDF and LiTFSI. The PVDF solid electrolyte is modified by forming a special deep eutectic solvent (DES) system with DMMSA and LiTFSI, which improves the ionic conductivity while reducing the interface resistance, maintains good thermal stability and has a simple processing method, and has the potential for large-scale application in the field of solid-state batteries.
[0012] Deep eutectic solvent (DES) refers to a type of solvent system that is a eutectic mixture formed by mixing two or more compounds at a specific molar ratio, and significantly reduces its melting point (lower than a single component). Fundamentally, the DES system is usually composed of a hydrogen bond acceptor and a hydrogen bond donor. Due to the presence of hydrogen bonds, the melting point of the eutectic mixture is reduced, and it can remain liquid over a wide temperature range. The present invention modifies the PVDF solid electrolyte by forming a special deep eutectic solvent (DES) system with DMMSA and LiTFSI. DMMSA with a sulfonamide group serves as a hydrogen bond donor for the DES system, and LiTFSI as a lithium salt serves as a hydrogen bond acceptor for the DES system. After mixing DMMSA and LiTFSI, they are liquid at room temperature and have a lower melting point.
[0013] According to a preferred embodiment of the first aspect, the molar ratio of the lithium salt to N,N-dimethylmethanesulfonamide is 1:1-7;
[0014] Further, the molar ratio of lithium salt to N,N-dimethylmethanesulfonamide is 1:1-5;
[0015] Furthermore, the molar ratio of the lithium salt to N,N-dimethylmethanesulfonamide is 1:2.5-3.5 (eg, 1:3).
[0016] According to a preferred embodiment of the first aspect, the mass ratio of the lithium salt to the polyvinylidene fluoride is 1:2.45-2.55.
[0017] According to a preferred embodiment of the first aspect, the mass ratio of the organic solvent to polyvinylidene fluoride is 1:0.061-0.063.
[0018] According to a preferred embodiment of the first aspect, the organic solvent is at least one of N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP).
[0019] According to a preferred embodiment of the first aspect, the PVDF-based solid electrolyte obtained by drying the gel solution comprises:
[0020] The gel solution is cast into a mold and dried at room temperature to form a film to obtain a PVDF-based solid electrolyte.
[0021] In a second aspect, the present invention provides a PVDF-based solid electrolyte, which is prepared by the preparation method of the PVDF-based solid electrolyte provided by the first aspect of the present invention.
[0022] In a third aspect, the present invention provides a quasi-solid-state battery, wherein the quasi-solid-state battery comprises a lithium iron phosphate positive electrode sheet, a solid electrolyte sheet and a metal lithium negative electrode sheet arranged in sequence; wherein the material of the solid electrolyte sheet is the PVDF-based solid electrolyte provided in the second aspect of the present invention.
[0023] According to a preferred embodiment of the third aspect, the quasi-solid-state battery further comprises an electrolyte solution dripped onto a first contact surface of the solid electrolyte sheet; wherein the first contact surface of the solid electrolyte sheet is a surface of the solid electrolyte sheet in contact with the lithium iron phosphate positive electrode sheet;
[0024] More preferably, based on the area of the first contact surface of the solid electrolyte sheet, the amount of the electrolyte solution dripped onto the first contact surface of the solid electrolyte sheet is 7-7.5 μL / mm 2 ;
[0025] More preferably, the electrolyte added dropwise onto the first contact surface of the solid electrolyte sheet is a lithium hexafluorophosphate electrolyte; further preferably, the electrolyte added dropwise onto the first contact surface of the solid electrolyte sheet comprises lithium hexafluorophosphate (LiPF6) and an organic solvent, wherein the organic solvent is selected from at least one of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), and based on the total mass of the electrolyte as 100%, the mass content of lithium hexafluorophosphate in the electrolyte is 12.9-13%.
[0026] According to a preferred embodiment of the third aspect, the quasi-solid-state battery further comprises an electrolyte solution dripped onto the second contact surface of the solid electrolyte sheet; wherein the second contact surface of the solid electrolyte sheet is a surface of the solid electrolyte sheet in contact with the negative electrode sheet of the metal lithium sheet;
[0027] More preferably, based on the area of the second contact surface of the solid electrolyte sheet, the amount of the electrolyte solution dripped onto the second contact surface of the solid electrolyte sheet is 7-7.5 μL / mm 2 ;
[0028] More preferably, the electrolyte added dropwise onto the second contact surface of the solid electrolyte sheet is a lithium hexafluorophosphate electrolyte; further preferably, the electrolyte added dropwise onto the second contact surface of the solid electrolyte sheet comprises lithium hexafluorophosphate (LiPF6) and an organic solvent, wherein the organic solvent is at least one of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), and based on the total mass of the electrolyte as 100%, the mass content of lithium hexafluorophosphate in the electrolyte is 12.9-13%.
[0029] According to a preferred embodiment of the third aspect, the lithium iron phosphate positive electrode sheet is prepared by the following method:
[0030] The active material lithium iron phosphate (LiFePO4), conductive carbon, polyvinylidene fluoride (PVDF), an organic solvent, and zirconium oxide beads are mixed to obtain a mixed slurry;
[0031] The mixed slurry is coated on an aluminum foil, and the organic solvent is removed by drying to obtain an aluminum foil sheet loaded with active material lithium iron phosphate (LiFePO4), and the lithium iron phosphate positive electrode sheet is obtained by cutting;
[0032] More preferably, the conductive carbon is conductive carbon Super P;
[0033] More preferably, the organic solvent is N-methyl-2-pyrrolidone (NMP);
[0034] More preferably, the mass ratio of lithium iron phosphate (LiFePO4), conductive carbon, and polyvinylidene fluoride (PVDF) is 7-8:1-2:1;
[0035] More preferably, the mass ratio of the organic solvent to lithium iron phosphate (LiFePO4) is 2.8:1.12-1.15.
[0036] According to a preferred embodiment of the third aspect, based on the area of the loading surface of the lithium iron phosphate positive electrode sheet on which the active substance lithium iron phosphate is loaded, the loading amount of the active substance lithium iron phosphate on the lithium iron phosphate positive electrode sheet is 1.6-2.0 mg·cm -2 .
[0037] According to a preferred embodiment of the third aspect, the thickness of the solid electrolyte sheet is 50-85 μm.
[0038] According to a preferred embodiment of the third aspect, the thickness of the lithium iron phosphate positive electrode sheet is 40-45 μm.
[0039] According to a preferred embodiment of the third aspect, the thickness of the metal lithium negative electrode sheet is 59-61 μm.
[0040] According to a preferred embodiment of the third aspect, the diameter of the solid electrolyte sheet is 16-20 mm.
[0041] According to a preferred embodiment of the third aspect, the diameter of the lithium iron phosphate positive electrode sheet is 10-14 mm.
[0042] According to a preferred embodiment of the third aspect, the diameter of the metal lithium sheet negative electrode sheet is 14-16 mm.
[0043] According to a preferred embodiment of the third aspect, the quasi-solid-state battery further includes a negative electrode shell, a spring, a first gasket, a second gasket and a positive electrode shell;
[0044] Assemble and package in the order of negative electrode shell, spring sheet, first gasket, metal lithium negative electrode sheet, solid electrolyte sheet, lithium iron phosphate positive electrode sheet, second gasket and positive electrode shell;
[0045] More preferably, the first gasket is made of stainless steel;
[0046] More preferably, the second gasket is made of stainless steel.
[0047] The technical solution provided by the present invention introduces DMMSA into the traditional PVDF-LiTFSI solid electrolyte system, and forms a special DES system to modify the PVDF solid electrolyte by N,N-dimethylmethanesulfonamide (DMMSA) and LiTFSI, thereby effectively reducing the crystallinity of the polymer in the electrolyte and promoting the rapid movement of the polymer chain, thereby helping the lithium salt to dissociate and transport faster, and improving the ionic conductivity of the solid electrolyte, up to 3.06×10 -4 Scm -1 , while ensuring thermal stability and electrochemical window, and effectively reducing interface impedance, and the processing method is simple, it has the potential to be widely used in the field of solid-state batteries. After assembling a quasi-solid-state battery with lithium iron phosphate as the positive electrode, the modified PVDF solid electrolyte quasi-solid-state battery showed a capacity of more than 138.8 mAh g -1 The first cycle discharge capacity is 100%, and it has considerable long cycle performance and rate performance.
[0048] Compared with the traditional PVDF solid electrolyte modification strategy, the modified PVDF-based solid electrolyte prepared in the present invention not only overcomes the defect of low safety of liquid DES electrolyte, but also significantly improves the ionic conductivity of PVDF-based solid electrolyte, reduces the interface impedance, and maintains good thermal stability, electrochemical properties and low-cost production advantages while improving performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a diagram of the solid electrolyte in Example 1.
[0050] Figure 2 This is a diagram of the assembly sequence of the quasi-solid-state battery in Example 1.
[0051] Figure 3A XRD spectra of solid electrolyte and PVDF powder.
[0052] Figure 3B DSC curves of solid electrolyte and PVDF powder.
[0053] Figure 4 This is the thermogravimetric curve of the solid electrolyte.
[0054] Figure 5A The cycle performance diagram of the quasi-solid-state battery provided for Comparative Example 1.
[0055] Figure 5B This is a cycle performance diagram of the quasi-solid-state battery provided in Example 1.
[0056] Figure 5C This is a cycle performance diagram of the quasi-solid-state battery provided in Example 2.
[0057] Figure 5D This is a cycle performance diagram of the quasi-solid-state battery provided in Example 3.
[0058] Figure 5E This is the discharge capacity diagram of the quasi-solid-state battery.
[0059] Fig. 5F Coulombic efficiency diagram of quasi-solid-state batteries.
[0060] Figure 6 This is the rate performance diagram of the quasi-solid-state battery.
[0061] Figure 7 This is the CV curve of the quasi-solid-state battery.
[0062] Figure 8 This is the LSV curve of the quasi-solid-state battery.
[0063] Fig. 9 The impedance spectrum of the battery before and after cycling.
[0064] Fig.10 This is the impedance spectrum of a symmetrical battery. DETAILED DESCRIPTION
[0065] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0066] Example 1
[0067] This embodiment provides a PVDF-based solid electrolyte and a quasi-solid-state battery.
[0068] The PVDF-based solid electrolyte is prepared by the following method:
[0069] In a glove box filled with argon atmosphere (water and oxygen content are all less than 0.01ppm), weigh the required sample polyvinylidene fluoride (PVDF) 0.375g, lithium salt lithium bistrifluoromethanesulfonyl imide (LiTFSI) 0.15g, N,N-dimethylmethanesulfonamide (DMMSA) 0.0644g (LiTFSI and DMMSA molar ratio 1:1), organic solvent N,N-dimethylformamide (DMF) 6g, add PVDF and LiTFSI into a screw-mouth glass sample bottle and drop DMF, put a magnet in a magnetic stirrer and stir at room temperature for 12h to fully dissolve, then add DMMSA into the sample bottle and continue stirring for 12h to obtain a gel solution, and evenly cast the gel solution into a PTFE dish with a diameter of 100mm. After drying at room temperature for 48h, a PVDF-based solid electrolyte with a thickness of about 70μm can be obtained, which is recorded as PVDF-DMMSA-1. Figure 1 shown.
[0070] The quasi-solid-state battery includes a negative electrode shell, a spring, a first gasket, a metal lithium sheet negative electrode sheet, a solid electrolyte sheet, a lithium iron phosphate positive electrode sheet, a second gasket, a positive electrode shell, an electrolyte dripped on a first contact surface of the solid electrolyte sheet, and an electrolyte dripped on a second contact surface of the solid electrolyte sheet. The first contact surface of the solid electrolyte sheet is the surface of the solid electrolyte sheet in contact with the lithium iron phosphate positive electrode sheet, and the second contact surface of the solid electrolyte sheet is the surface of the solid electrolyte sheet in contact with the metal lithium sheet negative electrode sheet.
[0071] Wherein, the material of the first gasket is stainless steel, and the material of the second gasket is stainless steel;
[0072] The solid electrolyte sheets are discs of 16 mm and 20 mm in diameter cut from the PVDF-DMMSA-1 solid electrolyte provided in this embodiment.
[0073] The electrolyte dripped on the first contact surface of the solid electrolyte sheet and the electrolyte dripped on the second contact surface of the solid electrolyte sheet are the same lithium hexafluorophosphate electrolyte, which is composed of lithium hexafluorophosphate (LiPF6) and organic solvents ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). Taking the total mass of the lithium hexafluorophosphate electrolyte as 100%, the mass content of LiPF6 in the lithium hexafluorophosphate electrolyte is 12.91%, the mass content of EC is 31.69%, the mass content of DEC is 25.49%, and the mass content of EMC is 29.91%. The amount of the electrolyte dripped on the first contact surface of the solid electrolyte sheet is 7.5 μL, and the amount of the electrolyte dripped on the second contact surface of the solid electrolyte sheet is 7.5 μL.
[0074] Among them, the metal lithium sheet negative electrode is a circular sheet with a diameter of 16mm and a thickness of 0.6mm.
[0075] Among them, the lithium iron phosphate positive electrode sheet is prepared by the following method: in a polytetrafluoroethylene box, the active material lithium iron phosphate (LiFePO4), conductive carbon Super P, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1. In this case, the mass of the active material LiFePO4 is 1.12g; then 2.80g of organic solvent N-methyl-2-pyrrolidone (NMP) is added, and then zirconium oxide balls are added to the polytetrafluoroethylene box and stirred for 10 minutes by a high-speed degassing mixer to obtain a mixed slurry; the mixed slurry is evenly scraped on a smooth aluminum foil (thickness of 22μm) with a scraper and placed in a vacuum drying oven at 60°C. The aluminum foil was dried at 400 °C for 24 h until the solvent NMP was fully volatilized to obtain an aluminum foil sheet (thickness of 42 μm) uniformly loaded with active substance lithium iron phosphate (LiFePO4), which was cut into circular sheets with a diameter of 10 mm using a slicer as lithium iron phosphate positive electrode sheets; the loading amount of active substance lithium iron phosphate on the lithium iron phosphate positive electrode sheet was 1.60 mg cm based on the loading surface area of the lithium iron phosphate positive electrode sheet (i.e., the surface area of the lithium iron phosphate positive electrode sheet on which the active substance lithium iron phosphate is loaded). -2 .
[0076] In a glove box filled with argon, the negative electrode shell, spring sheet, first gasket, metal lithium negative electrode sheet, solid electrolyte sheet (diameter 16 mm), lithium iron phosphate positive electrode sheet, second gasket and positive electrode shell were placed in the order (such as Figure 2 As shown in the figure) and packaged using a hydraulic button cell packaging machine to obtain a quasi-solid-state battery.
[0077] Example 2
[0078] This embodiment provides a PVDF-based solid electrolyte and a quasi-solid-state battery.
[0079] The preparation method of the PVDF-based solid electrolyte is different from that of Example 1 only in that the mass of N,N-dimethylmethanesulfonamide (DMMSA) is 0.1931 g (the molar ratio of LiTFSI to DMMSA is 1:3), and the prepared PVDF-based solid electrolyte is recorded as PVDF-DMMSA-3.
[0080] The difference between the quasi-solid-state battery and Example 1 is that the solid electrolyte sheet is prepared using the PVDF-DMMSA-3 PVDF-based solid electrolyte provided in this example.
[0081] Example 3
[0082] This embodiment provides a PVDF-based solid electrolyte and a quasi-solid-state battery.
[0083] The preparation method of the PVDF-based solid electrolyte is different from that of Example 1 only in that the mass of N,N-dimethylmethanesulfonamide (DMMSA) is 0.3218 g (the molar ratio of LiTFSI to DMMSA is 1:5), and the prepared PVDF-based solid electrolyte is recorded as PVDF-DMMSA-5.
[0084] The difference between the quasi-solid-state battery and Example 1 is that the solid electrolyte sheet is prepared using the PVDF-DMMSA-5 PVDF-based solid electrolyte provided in this example.
[0085] Comparative Example 1
[0086] This comparative example provides a PVDF-based solid electrolyte and a quasi-solid-state battery.
[0087] The preparation method of the PVDF-based solid electrolyte is different from that of Example 1 only in that N,N-dimethylmethanesulfonamide (DMMSA) is not added, and the prepared PVDF-based solid electrolyte is recorded as PVDF-LiTFSI.
[0088] The difference between the quasi-solid-state battery and Example 1 is that the solid electrolyte sheet is prepared using the PVDF-LiTFSI solid electrolyte provided in this example.
[0089] Comparative Example 2
[0090] This comparative example provides a PVDF-based solid electrolyte and a quasi-solid-state battery.
[0091] The preparation method of the PVDF-based solid electrolyte is different from that of Example 1 only in that N,N-dimethylmethanesulfonamide (DMMSA) and lithium salt lithium bistrifluoromethanesulfonyl imide (LiTFSI) are not added, and the prepared PVDF-based solid electrolyte is recorded as PVDF.
[0092] The difference between the quasi-solid-state battery and Example 1 is that the solid electrolyte sheet is prepared using the PVDF-based solid electrolyte PVDF provided in this example.
[0093] Comparative Example 3
[0094] This comparative example provides a PVDF-based solid electrolyte and a quasi-solid-state battery.
[0095] The preparation method of the PVDF-based solid electrolyte is different from that of Example 2 only in that cyclopentane sulfone is used to replace N,N-dimethylmethanesulfonamide (DMMSA), wherein the molar ratio of LiTFSI to cyclopentane sulfone is 1:3, and the prepared PVDF-based solid electrolyte is recorded as PVDF-cyclopentane sulfone-3.
[0096] The difference between the quasi-solid-state battery and Example 2 is that the solid electrolyte sheet is prepared using the PVDF-sulfolane-3 solid electrolyte provided in this comparative example.
[0097] Experimental Example 1
[0098] The XRD spectra of the PVDF-based solid electrolytes provided by Examples 1 to 3 and Comparative Examples 1 to 2 were tested respectively.
[0099] The results are as follows Figure 3A As shown. Figure 3A It can be seen that the main characteristic peaks of PVDF are mainly α phase, and the main characteristic peaks appear at around 2θ=18.4°, 20.1° and 26.6°. After adding LiTFSI and DMMSA, the main characteristic peaks of the solid electrolyte are still dominated by the peak shape of PVDF, and the characteristic peak of 20.1° is mainly retained. It is not easy to observe the crystallinity of the modified PVDF solid electrolyte and the unmodified PVDF solid electrolyte by peak intensity.
[0100] The thermal difference curves (DSC curves) of the PVDF-based solid electrolytes provided in Example 2 and Comparative Example 1-Comparative Example 2 were tested respectively.
[0101] The results are as follows Figure 3B As shown. Figure 3B It can be seen that among the melting peaks at the same temperature of around 165°C, the melting peak area of the solid electrolyte PVDF-DMMSA-3 is the smallest, which is lower than that of the solid electrolyte PVDF-LiTFSI and much smaller than that of the solid electrolyte PVDF. This indicates that the addition of DMMSA can significantly reduce the crystallinity of the solid electrolyte, thereby promoting the movement of polymer chain segments and enhancing its ionic conductivity.
[0102] Experimental Example 2
[0103] The STA7200 Thermal Analysis System produced by Hitachi was used to detect the difference in thermal stability of the PVDF-based solid electrolytes provided in Examples 1 to 3 and Comparative Example 1. The heating rate was 10°C min-1 and the temperature range was 25-800°C.
[0104] The results are as follows Figure 4 As shown. Figure 4 It can be seen that the modified solid electrolytes PVDF-DMMSA-1, PVDF-DMMSA-3, and PVDF-DMMSA-5 generally exhibit better thermal stability than the unmodified solid electrolyte PVDF-LiTFSI, and all of them only undergo significant decomposition after 300°C, which can meet the needs of commercial use.
[0105] Experimental Example 3
[0106] The quasi-solid-state batteries provided in Examples 1 to 3 and Comparative Example 1 were subjected to charge and discharge tests at a 1C rate using a Newway Battery Test System (CT-4008Tn-5V10mA) produced by Dongguan Newway Testing Technology Co., Ltd. The test environment temperature was room temperature, 25°C.
[0107] The results are as follows Figure 5A , Figure 5B , Figure 5C , Figure 5D , Figure 5E , Fig. 5F , Figure 6 shown. Figure 5A-5D They are respectively the charge and discharge curves of the quasi-solid-state batteries provided in Comparative Example 1 and Examples 1 to 3 at a rate of 1C, Figure 5E , Fig. 5F This is a comparison chart of the discharge capacity and coulomb efficiency of the quasi-solid-state batteries provided in Comparative Example 1 and Examples 1 to 3 at a 1C rate. Figure 5A-5F It can be seen that the modified PVDF-based solid electrolytes provided in Examples 1 to 3 show better cycle performance than the unmodified PVDF-based solid electrolytes provided in the comparative example. The first cycle discharge capacity and overall capacity are higher than those of the unmodified PVDF solid electrolyte. The 1:3 addition amount is optimal, and the first cycle discharge capacity is as high as 138.8 mAh g -1 , which is much higher than the first cycle of 116.9 mAh·g of the unmodified PVDF solid electrolyte provided in Comparative Example 1. -1 The specific capacity of the battery is 146.3 mAh g -1 , the Coulomb efficiency is almost 100%, the capacity retention rate after 100 cycles is 92.8%, and the capacity retention rate after 200 cycles is 84.5%.
[0108] The quasi-solid-state batteries provided in Example 1 to Example 3 and Comparative Example 1 were respectively subjected to charge and discharge tests at 0.1C, 0.5C, 1C, 2C, and 0.1C rates using a Newway Battery Test System (CT-4008Tn-5V10mA) produced by Dongguan Newway Testing Technology Co., Ltd. The test environment temperature was room temperature 25°C.
[0109] The results are as follows Figure 6 shown. Figure 6 The figure is a rate performance diagram of the quasi-solid-state battery provided by Comparative Example 1 and Examples 1 to 3. Figure 6 It can be seen that the modified PVDF-based solid electrolytes provided in Examples 1 to 3 exhibit higher capacity than the unmodified PVDF solid electrolyte provided in Comparative Example 1 at rates of 0.1C, 0.5C, 1C, and 2C, and still have a capacity retention rate of about 97% when returning from a high rate to 0.1C.
[0110] Therefore, it can be seen that the cyclic battery assembled with the modified PVDF-based solid electrolyte provided by the present invention has excellent commercial application potential.
[0111] Experimental Example 4
[0112] In a Solartron electrochemical workstation, the CV curves and LSV curves of the quasi-solid-state batteries provided in Example 2 and Comparative Example 1 were tested respectively.
[0113] The results are as follows Figure 7 , Figure 8 As shown. Figure 7 The CV curve provided shows that the modified PVDF-based solid electrolyte provided in Example 2 has a lower oxidation potential and a higher reduction potential, indicating that it is easier to form a better interface protection layer during the first cycle of battery charge and discharge. Figure 8 From the provided LSV curve, it can be seen that the modified PVDF-based solid electrolyte provided in Example 2 has a wider electrochemical window, reaching 4.7V, and can be applied to most high-voltage application scenarios.
[0114] Experimental Example 5
[0115] In a Solartron electrochemical workstation, the impedance spectra of the quasi-solid-state batteries provided in Example 2 and Comparative Example 1 were tested before and after one cycle.
[0116] The results are as follows Fig. 9 As shown. Fig. 9 From the intersection of the left side of the high-frequency semicircle and the X-axis, it can be seen that for the bulk resistance of the electrolyte, the modified PVDF-based solid electrolyte provided in Example 2 is only 4.25Ω, which is lower than the 4.99Ω of the unmodified PVDF-based solid electrolyte provided in Comparative Example 1.ct The modified PVDF-based solid electrolyte provided in Example 2 is higher than the unmodified PVDF-based solid electrolyte provided in Comparative Example 1, but after the first cycle of charge and discharge activation of the battery, the quasi-solid-state battery assembled with the modified PVDF-based solid electrolyte provided in Example 2 is reduced from 79.98Ω to 76Ω, while the quasi-solid-state battery assembled with the unmodified PVDF-based solid electrolyte provided in Comparative Example 1 is increased from 39.21Ω to 185.6Ω, indicating that the unmodified PVDF-based solid electrolyte provided in Comparative Example 1 cannot form a good interface contact in the first cycle of charge and discharge of the battery, but increases the interface impedance; while the modified PVDF-based solid electrolyte provided in Example 2 can effectively form a stable interface contact layer, which can improve the solid interface contact of the battery.
[0117] Experimental Example 6
[0118] In order to verify the speculation that the reduction in crystallinity reflected in the DSC curve can improve the ionic conductivity, symmetrical batteries were prepared using the solid electrolyte sheets with a diameter of 20 mm provided in Examples 1 to 3, Comparative Example 1, and Comparative Example 3, respectively. In a Solartron electrochemical workstation, the ionic conductivity of the symmetrical batteries prepared using the solid electrolyte sheets with a diameter of 20 mm provided in Examples 1 to 3, Comparative Example 1, and Comparative Example 3 was tested.
[0119] Among them, the difference between the symmetrical battery prepared by using the solid electrolyte sheet with a diameter of 20 mm provided by Example 1 to Example 3, Comparative Example 1 and Comparative Example 3 and the quasi-solid-state battery provided by Example 1 to Example 3, Comparative Example 1 and Comparative Example 3 is that the diameter of the solid electrolyte sheet used is 20 mm instead of 16 mm, and the positive electrode sheet does not use a lithium iron phosphate positive electrode sheet but a metal lithium sheet that is the same as the negative electrode sheet.
[0120] The impedance data of the symmetrical battery prepared using the solid electrolyte sheet with a diameter of 20 mm provided in Examples 1 to 3, Comparative Example 1 and Comparative Example 3 at 25°C are as follows: Fig.10 According to the formula σ=L / SR, it can be calculated that the ionic conductivity of PVDF-LiTFSI, PVDF-DMMSA-1, PVDF-DMMSA-3, PVDF-DMMSA-5, and PVDF-sulfolane-3 solid electrolytes are 1.70×10 -4 S cm -1 , 2.54×10 -4 S cm -1 , 3.06×10 -4 S cm -1 , 2.72×10 -4 S cm -1 ,8.21×10 -5 S cm-1 The DES system used in the technical solution of the present invention contains a sulfonamide functional group in DMMSA, which refers to a structure in which one end of the sulfonyl group is directly connected to a nitrogen atom, which is different from the sulfone functional group contained in another commonly used DES system (the two ends of the sulfonyl group are connected to a hydrocarbon group). Therefore, Comparative Example 3 also provides a DES-modified solid electrolyte prepared by using a typical sulfone compound cyclopentane at a ratio of 1:3. Fig.10 It can be seen that the DES-modified PVDF solid electrolyte of the DMMSA system has higher ionic conductivity and is better than that of the sulfolane system.
[0121] It can be seen from this that the modified PVDF-based solid electrolytes provided in Examples 1 to 3 have higher ionic conductivity, which is consistent with the predicted result found in the DSC curve in Experimental Example 5 that a decrease in crystallinity can improve ionic conductivity.
[0122] In summary, the present invention modifies PVDF by adding DMMSA and LiTFSI to form a special deep eutectic solvent, reduces the crystallinity of the electrolyte to promote the movement of polymer chains, and promotes the effective dissociation of lithium salts, thereby significantly improving the cycle performance, rate performance, and ionic conductivity of the PVDF-based solid electrolyte, and reducing the interfacial impedance of the battery; and while improving the battery performance, it will not reduce the thermal stability and electrochemical window of the electrolyte, and has good potential for commercial application.
[0123] The embodiments described above are for better explaining the present invention. For technical researchers in the field, it is not difficult to make various modifications to these embodiments without departing from the principles and spirit of the present invention. Therefore, the present invention is not limited to the embodiments herein. The improvements and changes made by those skilled in the art to the present invention according to the principles and spirit of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a PVDF-based solid electrolyte, wherein: The method includes: Mixing polyvinylidene fluoride, lithium salt lithium bis(trifluoromethanesulfonyl imide), N,N-dimethylmethanesulfonamide and an organic solvent to obtain a gel solution; The gel solution is dried to obtain a PVDF-based solid electrolyte.
2. The preparation method according to claim 1, wherein The molar ratio of lithium salt to N,N-dimethylmethanesulfonamide is 1:1-7; Preferably, the molar ratio of the lithium salt to N,N-dimethylmethanesulfonamide is 1:1-5; more preferably, the molar ratio of the lithium salt to N,N-dimethylmethanesulfonamide is 1:2.5-3.
5.
3. The preparation method according to claim 1, wherein The mass ratio of lithium salt to polyvinylidene fluoride is 1:2.45-2.55; and / or The mass ratio of the organic solvent to the polyvinylidene fluoride is 1:0.061-0.
063.
4. The preparation method according to claim 1, wherein The organic solvent is selected from at least one of N,N-dimethylformamide and N-methylpyrrolidone.
5. A PVDF-based solid electrolyte, which can be prepared by the preparation method of the PVDF-based solid electrolyte according to any one of claims 1 to 4.
6. A quasi-solid-state battery, wherein: The quasi-solid-state battery comprises a lithium iron phosphate positive electrode sheet, a solid electrolyte sheet and a metal lithium negative electrode sheet which are arranged in sequence; wherein the material of the solid electrolyte sheet is the PVDF-based solid electrolyte as described in claim 5.
7. The quasi-solid-state battery according to claim 6, wherein: The quasi-solid-state battery further comprises an electrolyte dripped onto the first contact surface of the solid electrolyte sheet; wherein the first contact surface of the solid electrolyte sheet is the surface of the solid electrolyte sheet in contact with the lithium iron phosphate positive electrode sheet; preferably, based on the area of the first contact surface of the solid electrolyte sheet, the amount of the electrolyte dripped onto the first contact surface of the solid electrolyte sheet is 7-7.5 μL / mm 2 ; Preferably, the electrolyte dripped onto the first contact surface of the solid electrolyte sheet is a lithium hexafluorophosphate electrolyte; The quasi-solid-state battery further comprises an electrolyte solution dripped onto the second contact surface of the solid electrolyte sheet; wherein the second contact surface of the solid electrolyte sheet is the surface of the solid electrolyte sheet in contact with the negative electrode sheet of the metal lithium sheet; preferably, based on the area of the second contact surface of the solid electrolyte sheet, the amount of the electrolyte solution dripped onto the second contact surface of the solid electrolyte sheet is 7-7.5 μL / mm 2 Preferably, the electrolyte dripped onto the second contact surface of the solid electrolyte sheet is lithium hexafluorophosphate electrolyte.
8. The quasi-solid-state battery according to claim 6, wherein: The lithium iron phosphate positive electrode sheet is prepared by the following method: Mixing active material lithium iron phosphate, conductive carbon, polyvinylidene fluoride, organic solvent, and zirconium oxide beads to obtain a mixed slurry; The mixed slurry is coated on an aluminum foil, and the organic solvent is removed by drying to obtain an aluminum foil sheet loaded with active material lithium iron phosphate, and the lithium iron phosphate positive electrode sheet is obtained by cutting; Preferably, the conductive carbon is conductive carbon Super P; Preferably, the organic solvent is N-methyl-2-pyrrolidone; Preferably, the mass ratio of lithium iron phosphate, conductive carbon, and polyvinylidene fluoride is 7-8:1-2:1; Preferably, the mass ratio of the organic solvent to the lithium iron phosphate is 2.8:1.12-1.15; Preferably, based on the area of the loading surface of the lithium iron phosphate positive electrode sheet on which the active substance lithium iron phosphate is loaded, the loading amount of the active substance lithium iron phosphate on the lithium iron phosphate positive electrode sheet is 1.6-2.0 mg·cm -2 .
9. The quasi-solid-state battery according to claim 6, wherein: The thickness of the solid electrolyte sheet is 50-85 μm; The diameter of the solid electrolyte sheet is 16-20 mm.
10. The quasi-solid-state battery according to claim 6, wherein: The quasi-solid-state battery also includes a negative electrode shell, a spring, a first gasket, a second gasket and a positive electrode shell; The negative electrode shell, the spring sheet, the first gasket, the metal lithium negative electrode sheet, the solid electrolyte sheet, the lithium iron phosphate positive electrode sheet, the second gasket and the positive electrode shell are assembled and packaged in this order.